2018
DOI: 10.1038/s41386-018-0073-1
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitor MS-275 restores social and synaptic function in a Shank3-deficient mouse model of autism

Abstract: Autism is a neurodevelopmental disorder characterized by social deficits and repetitive behaviors. Genetic screening has identified synaptic, transcriptional, and chromatin genes disrupted in autistic patients. Haploinsufficiency of Shank3, which encodes a scaffold protein at glutamatergic synapses, is causally linked to autism. Using a Shank3-deficient mouse model that exhibits prominent autism-like phenotypes, we have found that histone acetylation in the prefrontal cortex (PFC) is abnormally low, which can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 51 publications
(84 reference statements)
3
53
0
Order By: Relevance
“…Approximately 50% of TSC patients exhibit ASD 9 and it should be noted that recent reports reveal a role for increased HDAC activity in ASD-like social deficits in Shank3 -deficient mice 51,52 and in the BTBR T + tf/J (BTBR) mouse model of autism 53 . These studies extend the potential therapeutic benefits of HDACis in treating TSC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50% of TSC patients exhibit ASD 9 and it should be noted that recent reports reveal a role for increased HDAC activity in ASD-like social deficits in Shank3 -deficient mice 51,52 and in the BTBR T + tf/J (BTBR) mouse model of autism 53 . These studies extend the potential therapeutic benefits of HDACis in treating TSC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, SHANK3 mutations have been shown to account for ∼1% of all ASD cases (Leblond et al, 2014). Multiple lines of Shank3 -mutant mice and, more recently, rats that carry global, conditional and point mutations in Shank3 , have been generated and characterized, providing information about normal and disease-related functions of Shank3 (Bozdagi et al, 2010; Peca et al, 2011; Wang et al, 2011; Schmeisser et al, 2012; Yang et al, 2012; Han et al, 2013; Kouser et al, 2013; Lee et al, 2015; Speed et al, 2015; Jaramillo et al, 2016, 2017; Mei et al, 2016; Wang et al, 2016; Zhou et al, 2016; Harony-Nicolas et al, 2017; Vicidomini et al, 2017; Amal et al, 2018; Berg et al, 2018; Bey et al, 2018; Drapeau et al, 2018; Engineer et al, 2018; Fourie et al, 2018; Heise et al, 2018; Jin et al, 2018; Ma et al, 2018; Qin et al, 2018; Yoo et al, 2018; Zhu et al, 2018; Balaan et al, 2019; Rendall et al, 2019). These animals display diverse synaptic, neuronal, circuit and behavioral abnormalities, providing substantial insight into how Shank3 mutations lead to various phenotypic abnormalities in mice (Jiang and Ehlers, 2013; Harony-Nicolas et al, 2015; Sala et al, 2015; Ferhat et al, 2017; Monteiro and Feng, 2017; Mossa et al, 2017; Tan and Zoghbi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other HDACi, MS-275 has a long half-life and can enter the brain even at low doses, raising Ac-H3 levels in the brain ( 14 ). A recent study demonstrated that MS-275 improved autism-induced synaptic and social discrepancies through the epigenetic modulation of associated genes, such as surface NMDARs and actin regulators ( 27 ). Thus, MS-275 pre-treatment was used to inhibit HDAC1-3 and study its effect on MAPK signaling proteins, neuronal apoptosis and cognitive function following isoflurane exposure.…”
Section: Discussionmentioning
confidence: 99%